1991
DOI: 10.1007/bf00196347
|View full text |Cite
|
Sign up to set email alerts
|

Gramicidin in chromatophores of Rhodobacter sphaeroides

Abstract: Abstract. Chromatophores of Rhodobacter sphaeroideswere excited with light flashes to generate a transmembrane electrical potential difference. The electric relaxation was measured by electroehromic absorption changes as a function of added gramicidin. At low gramicidin/baeteriochlorophyll (BChl) molar ratios the decay of the electrochromic absorption changes showed a biphasic behaviour, with a fast phase relaxing at some gs, and a slow phase relaxing at more than 100 ms. This was attributable to a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The values determined in the present work for the size and the capacitance of the electric units are thus within the range of values characterizing a single chromatophore vesicle. Furthermore, the decay time of the membrane potential in the presence of gramicidin determined in this work is very similar to the decay time of the electrochromic absorption changes obtained by gramicidin titration of chromatophores from R. sphaeroides in solution [21]. From these good agreements it can be concluded that the surface of the support is covered by independent blisters formed by fusion of single chromatophores.…”
Section: Resultssupporting
confidence: 84%
“…The values determined in the present work for the size and the capacitance of the electric units are thus within the range of values characterizing a single chromatophore vesicle. Furthermore, the decay time of the membrane potential in the presence of gramicidin determined in this work is very similar to the decay time of the electrochromic absorption changes obtained by gramicidin titration of chromatophores from R. sphaeroides in solution [21]. From these good agreements it can be concluded that the surface of the support is covered by independent blisters formed by fusion of single chromatophores.…”
Section: Resultssupporting
confidence: 84%